Anti-Canadianism: Explaining the Deep Roots of a Shallow Phenomenon - Harrison, Trevor (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
Anti-Americanism is often said to be a central element of Canadian identity. Recently, however, its counterpart—anti-Canadianism—emerged in the United States. This article examines these expressions of anti-Canadianism, situating the phenomenon within the two countries' historical, ideological-discursive, and political relationships. The paper suggests anti-Canadianism in the United States stems from a mix of anti-French sentiment, a refusal to accept the distinctiveness of English-speaking Canada, and a growing divergence of value orientations between the two countries. The paper argues further that anti-Canadianism must be viewed (like its counterpart) according to its political uses on both sides of the border.